Differentiated ratings of perceived exertion at ventilatory threshold in children and adults - Mahon, A. D.; Gay, J. A.; Stolen, K. Q. (European Journal of Applied Physiology, 1998)
The purpose of this study was to examine overall, leg and chest ratings of perceived exertion (RPE) at ventilatory threshold (Thvent) in 16 children (mean age 10.9 years) and 17 adults (mean age 24.3 years). Thvent and maximum oxygen consumption (VO2 max ) were measured during a graded exercise test on a cycle ergometer. Overall, leg and chest RPE were obtained at the end of each exercise stage. VO2 max was 49.9 (8.5) and 47.1 (6.1) ml · kg-1· min-1 [mean (SD)] in the adults and children, respectively (P > 0.05). Relative to VO2 max , Thvent was 61.7 (5.3)% in the adults and 64.7 (5.2)% in the children (P > 0.05). Overall, leg, and chest RPE values at Thvent for the adults were 11.5 (2.6), 11.9 (2.5), and 10.5 (2.5), while for the children these values were 13.6 (2.2), 14.1 (2.2), and 12.6 (2.3), respectively. All RPE values were higher for the children (P < 0.05). These results suggest that children are able to discriminate levels of exertion in different parts of their body during graded exercise. Furthermore, children rate an intensity corresponding to Thvent to require a greater overall, leg and chest effort than adults exercising at a similar intensity. This indicates that children experience more pronounced cardiorespiratory and muscular sensations during this type of exercise.